The Comparison of Spark Motor Program and Developmental Gymnastic Instructional Program in Fundamental Skill Development in 6-8-Year-Old Children - Hakimeh Akbari (University of Tehran, 2013)
Fundamental motor skills are the bases of special motor skills. In addition tomaturation, environmental promotion can influence these skills. The aim of thisstudy was to investigate and compare the effect of developmental gymnasticinstructional program and Spark motor program as motor experiences onfundamental motor skills development in children aged between 6 and 8. For thispurpose, 120 children (6-8 years old) were selected from Tehran primary schoolsby cluster random sampling method. After the pretest (test of gross motordevelopment, second edition, Ulrich), the subjects were divided into three groupsof Spark motor program, developmental gymnastic instructional program andcontrol. The programs were performed for one year (36 weeks, one session perweek, 30 minutes per session). In the 37th week, the posttest was performed. Datawere analyzed by paired sample t test and one-way ANOVA. The results showedthat Spark program and gymnastic program outperformed the control group infundamental motor skills and locomotion (P˂0.05) and the difference between thetwo experimental groups was not significant. Spark program was more effectivethan gymnastic program and control group in the development of manipulationskills. Gymnastic program was more effective than the control group in thedevelopment of manipulation skills (P˂0.05). Thus, it can be concluded thatinstructional programs can be considered as a proper motor experience forchildren. These programs can be used to develop motor skills at schools through providing suitable opportunities for more training and presenting developmental motor tasks.